1979
DOI: 10.1002/jmor.1051600305
|View full text |Cite
|
Sign up to set email alerts
|

Origin and fate of germ cells in male and female embryos of Haplothrips verbasci (Osborn) (Insecta, Thysanoptera, Phlaeothripidae)

Abstract: Comparison of germ cells in male and female embryos of the arrhenotokous thrips, Haplothrips verbasci, yields the following observations: A mean of 11 cleavage energids enter the posterior pole plasm of the egg after the sixth cleavage division and apparently become pole cells when they take up polar granules in their cytoplasm. The cells proliferate asynchronously prior to and during anatrepsis to yield a mean of 36 germ cells in male embryos and 31 in females. Visible sexual differentiation of germ cells beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…In Polyneoptera, the embryo is formed by a pair of blastoderm regions with higher cellular density (e.g., Dermaptera: Shimizu, ; Embioptera: Jintsu, ; Phasmatodea: Bedford, ; Orthoptera: Miyawaki et al, ; Nakamura et al, ; Zoraptera: Mashimo et al, ; Grylloblattodea: Uchifune & Machida, ). In Palaeoptera and Acercaria (e.g., Ephemeroptera: Tojo & Machida, ; Odonata: Ando, ; Psocodea: Goss, ; Thysanoptera: Haga, ; Heming, ), cells near the posterior pole concentrate in one area and proliferate to form the embryo. This type is also found in the apterygote ectognathan orders Archaeognatha (Machida, Nagashima, & Ando, ) and Zygentoma (Masumoto & Machida, ), clearly suggesting that this is a plesiomorphic condition belonging to the groundplan of the Ectognatha and Pterygota.…”
Section: Discussionmentioning
confidence: 99%
“…In Polyneoptera, the embryo is formed by a pair of blastoderm regions with higher cellular density (e.g., Dermaptera: Shimizu, ; Embioptera: Jintsu, ; Phasmatodea: Bedford, ; Orthoptera: Miyawaki et al, ; Nakamura et al, ; Zoraptera: Mashimo et al, ; Grylloblattodea: Uchifune & Machida, ). In Palaeoptera and Acercaria (e.g., Ephemeroptera: Tojo & Machida, ; Odonata: Ando, ; Psocodea: Goss, ; Thysanoptera: Haga, ; Heming, ), cells near the posterior pole concentrate in one area and proliferate to form the embryo. This type is also found in the apterygote ectognathan orders Archaeognatha (Machida, Nagashima, & Ando, ) and Zygentoma (Masumoto & Machida, ), clearly suggesting that this is a plesiomorphic condition belonging to the groundplan of the Ectognatha and Pterygota.…”
Section: Discussionmentioning
confidence: 99%
“…Since germ cells arise at the posterior pole just after gastrulation in some hemimetabolous species [16], [67], [68], it is possible that factors that predispose posterior nuclei to take germline fate are also localized at the posterior pole in these species. The molecular nature of any such factor, and whether its role is direct or indirect, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological studies of three paraneopteran species, a book louse (Psocoptera (Goss, 1952)), a thrip (Thysanoptera (Heming, 1979)) and an aphid (Hemiptera (Chang et al, 2009)) suggested the presence of germ plasm in oocytes or early embryos, as did expression studies of vasa , piwi and nanos expression during asexual development of the pea aphid Acyrthosiphon pisum (Chang et al, 2006; Chang et al, 2007; Chang et al, 2009; Lu et al, 2011). However, A. pisum embryogenesis is highly modified relative to that of other hemimetabolous insects and even relative to other members of the same order (Miura et al, 2003).…”
Section: Introductionmentioning
confidence: 98%